2009
DOI: 10.1002/pbc.22285
|View full text |Cite
|
Sign up to set email alerts
|

Age, stage, and radiotherapy, but not primary tumor site, affects the outcome of patients with malignant rhabdoid tumors

Abstract: Our population-based study indicates that age at diagnosis, tumor stage, and use of radiotherapy favorably impact survival rates of patients with MRTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
110
2
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(127 citation statements)
references
References 19 publications
8
110
2
7
Order By: Relevance
“…At 6 months a PET scan was performed and the patient had no evidence of disease. [5,6,[10][11][12][13][14][15][16][17][18][19][20][21]. In a review of the English literature, 14 cases of primary MRT involving the soft tissues of the head and neck were identified [11][12][13][14][15][16][17][18][19][20][21] (Table 1).…”
Section: Case Reportmentioning
confidence: 99%
See 4 more Smart Citations
“…At 6 months a PET scan was performed and the patient had no evidence of disease. [5,6,[10][11][12][13][14][15][16][17][18][19][20][21]. In a review of the English literature, 14 cases of primary MRT involving the soft tissues of the head and neck were identified [11][12][13][14][15][16][17][18][19][20][21] (Table 1).…”
Section: Case Reportmentioning
confidence: 99%
“…One study by Sultan et al [10] found that radiation therapy, age at diagnosis (with children under 2 showing the worst prognosis) and tumor stage to be the most significant prognostic factors. Reports of overall survival rates of patients with MRT range from 20 to 33 % [5,10]. Distant metastasis has been reported and is more common in renal MRT [5,10].…”
Section: Case Reportmentioning
confidence: 99%
See 3 more Smart Citations